Section 22 unconscionability - a sauropod in need of life support - Griggs, L.; Webb, Eileen (QUT Publication, 2011)
The Full Federal Court decision in Allphones Retail Pty Ltd v Hoy Mobile Pty Ltd (2009) 178 FCR 57; ATPR 42-294 represents a step back towards an era where unconscionable conduct was not allowed to impinge on commercial certainty. Of the four judges who heard this matter three different approaches to the relationship of what is now s 22 of the Australian Consumer Law to s 243 were given. The paper concludes that the primary judge Rares J was the only one of the quartet who got it right. The other three approaches impose, using the criterion of causation, restrictive barriers on the operation of s 22 unconscionability. Regrettably, with the High Court refusing special leave to appeal and in the absence of any suitable test case to explore the parameters, s 22 remains underutilised and under threat of being cast in the same light as the sauropod - an assumption that it looms large in weight and height but in the absence of anyone sighting it, presumed extinct. For this reason, the Australian Competition and Consumer Commission is urged to identify an appropriate test case to explore the limits of s 22. If this is not done urgently, the present narrow, confining operation of the legislation will not only be out of step with Parliament's intent, but positively moving in another direction.